Mechanism of Ivughli salt dome exhumation, northwestern Iran - Alizadeh, Akram; Dargahi, Khatoon (Geology, ecology, and landscapes, 2025)
ABSTRACT The Ivughli salt dome, located in the West Azerbaijan province of Iran, is sourced in the Miocene Upper Red Formation, which includes salt and gypsum layers, red marl, and sandstone. The salt diapirs of West Azerbaijan are located along the North Tabriz Fault. Faults related to fractures around the Ivughli salt dome have displaced the folded layers and have caused subsidence in some parts of the salt dome. Based on the results of interferometry data, there are smaller and bigger elevation/subsidency rates with a total average of 4 mm for the whole body of the dome. The east of the dome shows high elevation and this may be due to the effect of a hidden fault that branches off the North Tabriz Fault. As well as the role of normal faults in the lower elevation of the western parts of the dome, there may have been subsidence related to surface washing and driven by erosion and agriculture in the region. Regarding the emplacement and shape of the Ivughli salt dome, it is young diapirism and currently acctive. In general, tectonic activity is still causing the rise of the Ivughli salt dome at a rate of movement that is not uniform across its structure.